Consolidating a research agenda for vaccine mandates. Issue 51 (5th December 2022) - Attwell, Katie; Rizzi, Marco; Paul, Katharina T.
Highlights: The pandemic pushed vaccine mandates to the forefront of global public health policy. This special issue synthesises the findings of research in the field. Scholars employ a range of methodologies to study speculative and real mandates. Scholars study vaccine mandates at different stages of the policy cycle. Scholars analyse mandates' impact on vaccine coverage rates and wider experiences. Abstract: A workshop on mandatory vaccination was pitched to the World Public Health Congress in 2019 and the resultant special issue was pitched to Vaccine in 2020. During this project, the COVID-19 pandemic pushed vaccine policy to the forefront of global public health policy, and the imposition of vaccine mandates prompted a new wave of scholarship in the field. This introductory article employs the heuristic of Lasswell's (1956) policy cycle to synthesise the findings of the articles in the special issue. It considers the temporal lifetime of mandates and highlights findings regarding: the emergence of mandates as a policy option, public support and policy instrument design, what matters in the implementation of mandates, and what we can learn from evaluating them. The second half of the paper categorizes the included papers in terms of what aspects of mandates they study and the methods they employ to do so, in order to formulate a guide for future researchers of vaccine mandates. Scholars study either speculative or existing mandates – research can address several stages of the policy cycle or just one of them, ranging from attitudinal research to implementation studies and impact studies. Historical and contextual studies that take deep dives into a particular mandate are a much needed resource for studying emerging mandates, too, and scoping and framework- building work will undoubtedly be valuable in understanding and appreciating the wealth of knowledge production in this growing field. This special issue can serve as a roadmap for a consolidation of this interdisciplinary research agenda, and provide a helpful resource for decisionmakers at this historical juncture.